2016
DOI: 10.1021/acs.analchem.6b01135
|View full text |Cite
|
Sign up to set email alerts
|

A Glutathione (GSH)-Responsive Near-Infrared (NIR) Theranostic Prodrug for Cancer Therapy and Imaging

Abstract: To reduce the side effects of chemotherapy, nontoxic prodrugs activated by the tumor microenvironment are urgently required for use in cancer treatment. In this work, we developed prodrug 4 for tumor-targeting treatment and imaging of the anticancer drug release in vivo. Taking advantage of the high glutathione (GSH) concentration in cancer cells, the disulfide bond in prodrug 4 was cleaved, resulting in the release of an active anticancer drug and a near-infrared (NIR) fluorescence dye turn-on. Furthermore, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 52 publications
3
110
0
Order By: Relevance
“…Stable hemicyanines with a hydroxyl group have recently been continually employed for preparing NIR probes, 8 but those with an amino group are seldom available except for some recent examples. 9 Here, we have successfully synthesized an amino hemicyanine (HCA) via two steps (Scheme S1†), and found that, similar to a hydroxyl hemicyanine, 8 amino substitution by leucine can efficiently quench the hemicyanine’s fluorescence, producing an extremely low background fluorescence, which is expected to afford high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Stable hemicyanines with a hydroxyl group have recently been continually employed for preparing NIR probes, 8 but those with an amino group are seldom available except for some recent examples. 9 Here, we have successfully synthesized an amino hemicyanine (HCA) via two steps (Scheme S1†), and found that, similar to a hydroxyl hemicyanine, 8 amino substitution by leucine can efficiently quench the hemicyanine’s fluorescence, producing an extremely low background fluorescence, which is expected to afford high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, turn-onN IR fluorescent xanthene-cyanine dyes were recently designedf or spectrofluorometric and imaging-based detection of peroxynitrite, [13] fibroblasts, [14] aminopeptidase, [15,16] nitroxyl, [17] hydrogen polysulfide, [18] carboxylesterase, [19] hypochlorousa cid, [20] and glutathionine. [21,22] These dyes were also proposed for keloid diagnosis [23] and chemophotodynamic therapy. [24] However, the reported xanthene-cyanine dyesd id not contain reactive functionalities for binding to at argeting carrier and, until now,n one of them have been used for fluorescence TDD monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Synthetic small molecular fluorescent probesh ave been confirmed that were superior tools for trackingH OCl due to their high sensitivity,s electivity and easy manipulation. [15][16][17][18][19][20][21][22][23][24][25][26][27] Fluorescence imaging has been considered to be ah igh biocompatible imaging technique andh as been widely used ford etection of specific speciesa tt he cellular level for its noninvasive, realtime visualization, and high spatiala nd temporal resolution. [28][29][30][31][32][33] The conjunction of fluorescent probe and fluorescence imaging could provide us powerful tools for visualization of biologically relevant species.H ence, the fluorescent probesw ith high selectivity and sensitivity would able to trace the endogenousH OCl in living organisms.…”
Section: Introductionmentioning
confidence: 99%